Conditional Regard in the Classroom: A Double-Edged Sword - Kanat-Maymon, Yaniv; Shoshani, Anat; Roth, Guy (Frontiers in Psychology, 2021)
Teachers’ conditional positive and negative regard are widely endorsed teaching practices aimed to enhance students’ involvement and achievement in school. Previous research has mostly tapped the need frustration and harmful psychological well-being implications of these practices. Yet knowledge of their specific effects on school engagement is scant. This study investigated the association between students’ perceptions of homeroom teachers’ conditional positive and negative regard and their behavioral engagement, while considering the levels at which these practices are conceptualized and operate (a teacher characteristic and a student characteristic). Participants were n=2533 students from 107 classes in the 7th to 10th grades. Multilevel analysis found conditional positive regard was positively associated with school engagement while conditional negative regard was inversely related. These findings were obtained at both the within- and between-class levels. Based on the findings, we argue conditional regard is a double-edged sword. Consistent with previous research, we suggest conditional negative regard has an undermining effect, and we point to conditional positive regard’s potential to enhance engagement. Lastly, we discuss the importance of the level of analysis and the alignment of theory with measurement.